Developing Business Students ’ Learning Performance in Chongqing, China - Zou, Sixiao (Scholar: Human Sciences, 2025)
Purpose: This study examines the factors influencing students' learning performance, specifically focusing on Instructor Attitude toward Learners (AI), Instructor Technical Competence (TC), Motivation (MV), Self-Efficacy (SE), Behavioral Engagement (BE), Cognitive Engagement (CE), and Emotional Engagement (EE). Additionally, the research seeks to identify effective strategies for enhancing students' learning outcomes. Data, Materials, and Methodology: The validity of the study was ensured through the use of the index of item-objective congruence, while a pilot test (n = 30) was conducted to assess reliability using cronbach’s alpha. Data from 160 valid responses were analyzed using multiple linear regression to explore the significant relationships between the variables. A group of 25 students participated in a 10-week intervention design implementation (IDI) to further explore these relationships. Quantitative results from the pre-IDI and post-IDI phases were compared using a paired-sample t-test. Results: the study revealed that AI, TC, MV, SE, and EE significantly impact learning performance, as demonstrated by MLR, while BE and CE showed no significant effect. Furthermore, the paired-sample t-test indicated a significant improvement in learning performance between the post-IDI and pre-IDI stages. Findings: The study successfully implemented an intervention that incorporated five key influencing factors, leading to a marked improvement in the learning performance of business students in Chongqing, China.